Communal Solidarity and Familial Bonds as Social Capital for Catechetical Ministry - Agustinus Manfred Habur; Marselina Y. Luju; Adrianus Jebarus (Interdisciplinary Social Studies, 2025)
This study explores how communal solidarity and familial bonds function as forms of social capital that strengthen catechetical ministry in rural Catholic communities, drawing evidence from the pastoral reality of Stasi Rondo Woing. Although the community faces persistent challenges—such as limited catechist formation, low participation, and geographical constraints—the research reveals that deeply rooted cultural values of mutual cooperation, kinship, and shared responsibility provide a powerful foundation for revitalizing faith formation. Using a qualitative approach involving interviews, observations, and documentation, the study shows that these social capital dimensions significantly shape how catechesis is received, practiced, and sustained. Communal solidarity encourages collective engagement in catechetical gatherings, while family-based relational networks foster intergenerational transmission of faith and leadership emergence within small Christian communities. When catechesis is integrated into these relational and cultural structures, it becomes more relevant, participatory, and transformative, enabling the community to take active ownership of its spiritual development. This study concludes that leveraging communal and familial social capital is essential for building resilient and empowered catechetical ministries in rural settings, offering a model that aligns with contextual pastoral approaches and supports long-term ecclesial vitality.